A reconfiguração do ensino superior brasileiro a partir dos anos 1990: um estudo sobre o processo de expansão/interiorização na Universidade Federal do Maranhão via Reuni - RIBEIRO, Welline Dayane Reis (2021)
This research deal with the reconfiguration of higher education from the 1990s, considering the expansion process that took place at the Federal University of Maranhão via Reuni (2007-2012). Therefore, it was established as a general objective to analyze the expansion/internalization process in the Federal University of Maranhão from the implementation of Reuni. And as specific objectives to identify the historical aspects of higher education in Brazil between the 30s and 80s; analyze the policies and programs resulting from the processo of expansion of Brazilian higher education in the FHC and Lula administrations; analyze the actions implemented by Reuni at UFMA, considering their consequences for higher education on the continent’s campuses. The research is characterized as qualitative and documentar, seeking to respond to the proposed objectives through the analysis of documents prepared and disseminated by the Ministry of Education (MEC), Secretariat of Higher Education (SESu), National Association of Directors of Federal Institutions of Higher Education (Andifes) and Federal University of Maranhão, among others related to the object. It was also used as a theoretical basis the writings of authors such as Chauí (20010; Santos (2005); Bresser Pereira (1991); Dutra (2017); Sousa and Coimbra (2015;2017), among others. The methodological approach used was configured in a critical perspective of reality, considering two fundamental concepts addressed by Chagas (2011); research and exhibition. The first can be characterized as the research itself and the second the presentation of results. From the research, it was found that the process of expansion/internalization of Ufma via Reuni was marked by the intensification of neoliberal actions and policies, whose interests overlapped the rights conquered by unions and the in academic community in favor of public higher education, free and quality. In this sense, although the Program constitutes a policy of access and permanence of students in Brazilian universities, having achieved significant numbers of vacancies and enrollments from the opening of new courses, in the Maranhão scenario, investments in infrastructure and human resources did not keep up with the growth reached, which created obstacles to the permanence of many students in the courses. It was also found that the lack of infrastructure and human resources on the campuses in the interior of the state compromised the inseparability of the teaching-research-extension tripod, having also contributed to the precariousness of the campuses themselves; as well as teaching work and academic training of students.